Star Light, but Why Not So Bright? A Process Model of How Incumbents Influence Star Newcomer Performance - Boekhorst, Janet A.; Basir, Nada; Malhotra, Shavin (Academy of Management Review, 2024)
Star performers do not always sustain their performance edge after moving to new organizations. We offer an important explanation for whether star performers may flourish or flounder when they join a new team. Integrating insights from attribution theory and social comparison research, we present a process model explaining how incumbents make sense of star newcomer status. We propose that incumbents determine whether the star newcomer attained their star status through internal factors (e.g., ability, grit) or external factors (e.g., luck, affiliation), which gives rise to one of four distinct emotions: optimism, inspiration, shame, or envy. Incumbents who feel optimism or inspiration attempt to enhance their status through learning or helping behaviors that subsequently facilitates star newcomer performance, whereas incumbents who feel shame or envy seek to protect their status through withdrawal or destructive behaviors that hinder star newcomer performance. We further propose that the effect of incumbent behaviors on star newcomer performance is particularly likely when there is a high need for task-related interactions and complementary skills among team members. Our theoretical framework helps to advance the star newcomer literature by examining the largely overlooked influence of incumbents and highlighting the cognitive process that precedes their behavior towards star newcomers.